Bacteria-driven phthalic acid ester biodegradation: Current status and emerging opportunities. (September 2021) - Hu, Ruiwen; Zhao, Haiming; Xu, Xihui; Wang, Zhigang; Yu, Ke; Shu, Longfei; Yan, Qingyun; Wu, Bo; Mo, Cehui; He, Zhili; Wang, Cheng
Highlights: This review assessed the contamination levels of PAE in various ecosystems. Overviewed the current status of PAE-degrading bacterial isolates and communities. Discussed the challenges for understanding in situ PAE biodegradation mechanisms. Proposed a guide of building synthetic community to decipher interaction mechanism. Abstract: The extensive use of phthalic acid esters (PAEs) has led to their widespread distribution across various environments. As PAEs pose significant threats to human health, it is urgent to develop efficient strategies to eliminate them from environments. Bacteria-driven PAE biodegradation has been considered as an inexpensive yet effective strategy to restore the contaminated environments. Despite great advances in bacterial culturing and sequencing, the inherent complexity of indigenous microbial community hinders us to mechanistically understand in situ PAE biodegradation and efficiently harness the degrading power of bacteria. The synthetic microbial ecology provides us a simple and controllable model system to address this problem. In this review, we focus on the current progress of PAE biodegradation mediated by bacterial isolates and indigenous bacterial communities, and discuss the prospective of synthetic PAE-degrading bacterial communities in PAE biodegradation research. It is anticipated that the theories and approaches of synthetic microbial ecology will revolutionize the study of bacteria-driven PAE biodegradation and provide novel insights for developing effective bioremediation solutions.